Pelatihan Penguatan Peran Badan Permusyawaratan Rakyat Nagari (BPRN) dalam Mendukung Penyelenggaraan Pemerintahan Nagari di Nagari Sumanik Kabupaten Tanah Datar - Ria Ariany; Desna Aromatica; Hendri Koeswara; Ilham Aldelano Azre; Kusdarini Kusdarini; Muhammad Ichsan Kabullah; Misnar Sitriwanti; Roni Ekha Putera; Rozidateno P Hanida; Syamsurizaldi Syamsurizaldi; Wewen Kusumi Rahayu; Yoserizal Yoserizal (Warta Pengabdian Andalas, 2019)
After the enactment of the Village Law which is full of various new policies, it also has implications for the Village Consultative Body (BPD) with changes in the position, duties, functions and authority of the BPD. One of them is the issuance of Permendagri No. 110/2016 concerning BPD, and most recently in the context of West Sumatra the issuance of the Regional Regulation of West Sumatra Province No 7/2018 concerning Nagari. This Perda is claimed to be the first indigenous village regulation in Indonesia that wants to show the existence of Nagari "Asli" vis a vis with the implementation of modern village government in the implementation of public services. On the other hand, the weak role and function of BPD in running village government still occurs, including Nagari Sumanik. This dedication activity was to provide an understanding of the shifting position of BPRN; increase the understanding of BPRN members regarding their roles, functions, duties and authorities; and strengthening the role of BPRN in supporting the administration of the nagari government. The method of implementing community service included 3 (three) stages, namely; 1) Preparation; 2) Implementation; and, 3) Program evaluation or reflection on activities. Not all Regencies / Cities have responded to the policies of the Nagari Government in West Sumatra, including the Tanah Datar District, so this service activity is important for BPRN Sumanik, where not all members have a government background in strengthening their capacity to carry out their duties and functions and anticipate changes in policy.